2021
DOI: 10.1017/jfm.2020.968
|View full text |Cite
|
Sign up to set email alerts
|

On the statistical properties of surface elevation, velocities and accelerations in multi-directional irregular water waves

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 31 publications
(97 reference statements)
5
24
0
Order By: Relevance
“…They are reported in figure 3(b) based on the typical experimental values S = K − 3 = 0.2 from table 1. As observed in Klahn, Madsen & Fuhrman (2021), they both underestimate large positive values and fail to capture large negative ones (for which the p.d.f. is either undefined, as for the second-order Gram-Charlier approximation, or largely above the experimental data, as for the third-order approximation).…”
Section: Probability Density Functions (Pdfs)mentioning
confidence: 78%
See 2 more Smart Citations
“…They are reported in figure 3(b) based on the typical experimental values S = K − 3 = 0.2 from table 1. As observed in Klahn, Madsen & Fuhrman (2021), they both underestimate large positive values and fail to capture large negative ones (for which the p.d.f. is either undefined, as for the second-order Gram-Charlier approximation, or largely above the experimental data, as for the third-order approximation).…”
Section: Probability Density Functions (Pdfs)mentioning
confidence: 78%
“…where (Fedele & Tayfun 2009). Previous studies have only tested this result in the linear limit in which η C = 0 (Soquet-Juglard Klahn et al 2021). The normalized elevation η(t)/η(0) computed from (6.1) with both η C = 0 and η C = 1.25H s is reported in figure 6, along with experimental and numerical values for crests such that η C > 1.25H S .…”
Section: Shape Of Large Crestsmentioning
confidence: 93%
See 1 more Smart Citation
“…Drawing on the fact that irregular wave fields in some sense tend to become more nonlinear when the directional spread decreases (e.g. Onorato et al [13] and Toffoli et al [14]) this result could to some degree have been anticipated from the results Klahn et al [26], who have recently shown that the variance of the Eulerian velocity at the surface decreases with nonlinearity (see e.g. their table 3).…”
Section: (B) Variance Of the Eulerian Velocitymentioning
confidence: 91%
“…(2021 b ), it was observed that strongly non-Gaussian statistics for both surface elevation and horizontal velocity fields are triggered by abrupt depth changes. Recent studies by Klahn, Madsen & Fuhrman (2021 a , b ) consider statistical properties of surface elevation, velocity field, acceleration and forces on a vertical column in deep water that show the deviation from Gaussian statistics as the wave steepness increases.…”
Section: Introductionmentioning
confidence: 99%